PERSONALITY AND PROFESSIONAL TRAITS: HOW INTERPERSONAL CHARACTERISTICS DEFINE SOCIAL WORKERS - Alina COSTIN (International Journal of Social and Educational Innovation, 2024)
It is considered that self-awareness is a fundamental element in personal and professional development, especially in social assistance, where constant contact with the other implies self-discovery, self-knowledge, reflection, change (Alicke, Zhang, Stephenson, 2020). In this context of the need for self-knowledge and understanding, the objective of this paper is to highlight the existing differences according to gender and self-acceptance in terms of interpersonal characteristics developed early in the family: "Feeling of social communion - prosocial", "Agreement - compliance", "Taking the lead - leader", "Desire for recognition - approval" and "Being on guard - caution", dimensions measured with the BASIS-A questionnaire.